Evaluation of foliage potted plants for Northern plains - JAIN, RITU; SINGH, M K; VANLALRUATI, VANLALRUATI (The Indian Journal of Agricultural Sciences, 2019)
Pollution is increasing at an alarming rate, especially in cities. The pollution may be air pollution (outdoor or indoor), noise pollution, water pollution or soil pollution which directly affects human health as well as work efficiency. In order to reduce air pollution indoor or outdoor, there is a great demand of potted plants. Plants helps in reducing carbon dioxide, benzene and nitrogen dioxide levels, and also increase humidity and keep the temperature down. India is bestowed with different agro climatic conditions and evaluation of potted plants for their suitability for different agro climatic zones has not been done. Most foliage plants are tropical in nature and the movement of these plants to subtropical regions will affect their growth. Therefore, the present investigation was carried out during 2014–16 at Division of Floriculture and Landscaping, Indian Agricultural Research Institute, New Delhi to identify the plant species suitable for Delhi and Northern plains. For this purpose twelve species/varieties of different potted plants were used.The potted plants were kept under two conditions—glasshouse and open for the evaluation of growth and development. Based on different morphological traits like plant height, spread, number of branches, leaves and biomass, it was observed that plants like song of India, Philodendron xanadu, money plant, Syngonium, Aglaonema, Cardboard palm and Crotons were suitable for indoor conditions while Dragon tree, Areca palm, Cordyline and Araucaria were suitable for outdoor conditions. However, China palm was found bestfor both indoor and outdoor conditions under Northern plains.